2012
DOI: 10.1172/jci63563
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic sortilin regulates both apolipoprotein B secretion and LDL catabolism

Abstract: Genome-wide association studies (GWAS) have identified a genetic variant at a locus on chromosome 1p13that is associated with reduced risk of myocardial infarction, reduced plasma levels of LDL cholesterol (LDL-C), and markedly increased expression of the gene sortilin-1 (SORT1) in liver. Sortilin is a lysosomal sorting protein that binds ligands both in the Golgi apparatus and at the plasma membrane and traffics them to the lysosome. We previously reported that increased hepatic sortilin expression in mice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
233
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(258 citation statements)
references
References 40 publications
14
233
1
5
Order By: Relevance
“…As SorLA, in contrast to apoA-V, is not primarily expressed in the liver, it is likely that the receptor participates in endocytic functions involving apoA-V rather than in its intracellular processing . Sortilin, on the other hand, is abundantly expressed in the liver; further studies are needed to ascertain whether apoA-V plays a role in VLDL secretion, as recently suggested ( 67 ). In summary, our study strongly suggests a causal relationship between three novel APOA5 mutations and the hypertriglyceridemia found in the patients through impairment of different apoA-V functions, some of which are of unclear (patho)physiologic signifi cance at this point.…”
Section: Discussionsupporting
confidence: 64%
“…As SorLA, in contrast to apoA-V, is not primarily expressed in the liver, it is likely that the receptor participates in endocytic functions involving apoA-V rather than in its intracellular processing . Sortilin, on the other hand, is abundantly expressed in the liver; further studies are needed to ascertain whether apoA-V plays a role in VLDL secretion, as recently suggested ( 67 ). In summary, our study strongly suggests a causal relationship between three novel APOA5 mutations and the hypertriglyceridemia found in the patients through impairment of different apoA-V functions, some of which are of unclear (patho)physiologic signifi cance at this point.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, sortilin has been shown to bind apolipoprotein A-V and lipoprotein lipase 32,33) . The effect of sortilin on very low-density lipoprotein (VLDL) synthesis, as determined by overexpression and knockdown studies, is conflicting 11,34,35) . Musunuru et al 11) reported that sortilin reduced VLDL synthesis and thereby reduced LDL cholesterol levels, whereas Kjolby et al 34) reported that sortilin increased VLDL synthesis and thereby increased LDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Musunuru et al 11) reported that sortilin reduced VLDL synthesis and thereby reduced LDL cholesterol levels, whereas Kjolby et al 34) reported that sortilin increased VLDL synthesis and thereby increased LDL cholesterol levels. Strong et al 35) reported that increased hepatic sortilin expression reduced hepatic apolipoprotein B secretion and increased LDL catabolism, an increase in the expression of PCSK9 19) , counteracting the beneficial effects of statins. The mechanism underlying PCSK9 degradation of LDL receptors is extremely complex.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, this working model was challenged by studies in two independent mouse models with ubiquitous genetic inactivation of Sort1 in which loss of sortilin reduced (rather than increased) circulating cholesterol levels 14,39 . Based on the experimental model, several mechanisms are currently discussed how sortilin may impact cholesterol homeostasis, all of which suggest a function for this receptor in control of hepatic lipoprotein handling (Fig.…”
Section: Sortilin a Risk Factor For Hypercholesterolemia And Myocardmentioning
confidence: 99%
“…Circulating LDL are cleared by the LDL receptor in the liver and other tissues 40 . Proposed functions for sortilin in reducing plasma cholesterol comprise its action as a hepatic clearance receptor for LDL 39,41 or a role in anterograde sorting of nascent lipoprotein particles from the TGN to lysosomes, effectively reducing the output of VLDL by the liver 38,42 . In contrast, a possible activity of sortilin in increasing plasma cholesterol involves its ability to facilitate secretion of VLDL from hepatocytes 14 .…”
Section: Sortilin a Risk Factor For Hypercholesterolemia And Myocardmentioning
confidence: 99%